A META-ANALYTIC REVIEW OF PSYCHOLOGICAL PERSPECTIVES IN VISUAL AND PERFORMING ARTS IN MOVIES - Solanki, Nayan; Parmar, Vishalkumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This meta-analysis examines the psychological dimensions of visual and performing arts in movies released between 2010 and 2020. By synthesizing research on the cognitive, emotional, and social aspects of filmmaking and audience reception, this study explores the psychological principles that shape cinematic storytelling, performance, and viewer engagement. The findings provide insights into how movies serve as both a medium of artistic expression and a reflection of societal psychological dynamics, offering implications for filmmakers, psychologists, and cultural analysts.